PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II.B SDN 115 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem in this research is the low learning outcomes IPA ,. It can be seen from the results of student learning students only 14 students (41.1%), which reached KKM of 34 students, who do not reach KKM amounted to 20 (58.8%) students from 34 students with an average value of 64 , 8 and KKM specified value is 75. Berdasararkan these problems need to be done peneliiantinakan class by implementing cooperative learning model. This research aims to improve learning outcomes II.B grade science students SDN 115 Pekanbaru the number of students as many as 34 students consisting of 19 male students and 15 female students. This research was conducted as II cycles, in each cycle consisted of two meetings and one meeting. Dengsn implementation of cooperative learning model, can improve student learning outcomes IPA, it is seen from peningktan learning outcomes of students learning base score is an average of 64.8 increased by 15.7% to 76.4. Results of the second daily test scores of students increased from the base by an average of 76, 4 increased by 9.8% to 83.9. So every cycle of increased learning outcomes.The percentage of activity the first meeting of the first cycle as much as 58.3% to 66.6% the second meeting, the meeting IV suklus II to 91.6% at the V meeting of 100%.Ativitas students I cycle I as much as 54.1%, 62.5% the second meeting, the fourth meeting of the second cycle of 83.3%, meeting V 100%. Based on the results of this study concluded that the implementation of cooperative learning model, can improve student learning outcomes II.B grade SDN 115 Pekanbaru.Keywords: Cooperative Learning Model, IPA Student Learning Outcomes2